Research on the Problem and Solutions to Formation of Communication Skills - Iskandarova Aybibi Raximbayevna; Amanlikova Nafisa Raxmatullayevna (Genius Journals, 2023)
Our article discusses the problem of designing the communication space of students and future teachers as a means of improving pedagogical communication. The authors show approaches; You will get acquainted with the semantic accents to understand the communicative abilities and the conditions of their appearance
Keywords: Communicative connections; interpersonal communication; psychological organization